2006
DOI: 10.1007/s11258-006-9150-3
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitous genetic diversity in ISSR markers between and within populations of the asexually producing moss Pleurochaete squarrosa

Abstract: Abstract. This paper provides an analysis of genetic\ud variability in local populations of the clonal\ud moss Pleurochaete squarrosa, a Mediterranean\ud moss typical of post-fire recovery, and characterised\ud by asexual reproduction. ISSR (Internal\ud Simple Sequence Repeats) primers and trnLUAA\ud (intron of plastid gene for Leu tRNA) length\ud polymorphism were employed to evaluate genetic\ud structure in five southern Italy populations of this\ud moss. Both molecular tools highlight high values\ud of gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 37 publications
2
22
0
Order By: Relevance
“…Genetic variation is investigated by using internal simple sequence repeat (ISSR), which are molecular markers already employed by other authors Hassel et al 2005;Spagnuolo et al 2007) in studies concerning moss populations, providing easily available data, to obtain currently used molecular indices and information on the genetic structure of the investigated populations. All results are discussed in relation to population ecology and habitat disturbance and fragmentation.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic variation is investigated by using internal simple sequence repeat (ISSR), which are molecular markers already employed by other authors Hassel et al 2005;Spagnuolo et al 2007) in studies concerning moss populations, providing easily available data, to obtain currently used molecular indices and information on the genetic structure of the investigated populations. All results are discussed in relation to population ecology and habitat disturbance and fragmentation.…”
Section: Introductionmentioning
confidence: 99%
“…At this site we have already carried out a local-scale analysis (Spagnuolo et al 2007). For the small-scale analysis, 56 shoots were analysed in a grid of 35 cm 9 40 cm with mesh of 5 cm 9 5 cm ( Fig.…”
Section: Small Scalementioning
confidence: 99%
“…Lindb. (Pottiaceae) exhibits a high level of genetic diversity; spore and propagule recruitment, the modality of vegetative reproduction and somatic mutations were suggested among the most probable causes of the high intra-specific molecular diversity observed (Spagnuolo et al 2007). For this species, Grundmann et al (2006Grundmann et al ( , 2007Grundmann et al ( , 2008 reported a differentiation between American and European populations, limited gene flow, and a higher genetic diversity in the Mediterranean Basin than that observed in the rest of Europe, where a pattern of postglacial recolonisation from the Iberian Peninsula and the Balkans is proposed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations